Individual, social, and environmental factors affecting salivary and fecal cortisol levels in captive pied tamarins (Saguinus bicolor). Issue 8 (1st August 2019) - Price, Eluned; Coleman, Rob; Ahsmann, Judith; Glendewar, Gale; Hunt, Jenna; Smith, Tessa; Wormell, Dominic
Abstract: Pied tamarins ( Saguinus bicolor ) are endangered New World primates, and in captivity appear to be very susceptible to stress. We measured cortisol in 214 saliva samples from 36 tamarins and in 227 fecal samples from 27 tamarins, and investigated the effects of age, sex, pregnancy, rearing history, social status, weight, group composition, and enclosure type using generalized linear mixed models. There was no effect of age on either fecal or salivary cortisol levels. Female pied tamarins in late pregnancy had higher fecal cortisol levels than those in early pregnancy, or nonpregnant females, but there was no effect of pregnancy on salivary cortisol. Females had higher salivary cortisol levels than males, but there was no effect of rearing history. However, for fecal cortisol, there was an interaction between sex and rearing history. Hand‐reared tamarins overall had higher fecal cortisol levels, but while male parent‐reared tamarins had higher levels than females who were parent‐reared, the reverse was true for hand‐reared individuals. There was a trend towards lower fecal cortisol levels in subordinate individuals, but no effect of status on salivary cortisol. Fecal but not salivary cortisol levels declined with increasing weight. We found little effect of group composition on cortisol levels in either saliva or feces, suggesting that as long as tamarins are housed socially, the nature of the group is of less importance. However, animals in off‐show enclosures had higher salivary and fecal cortisol levels than individuals housed on‐show. We suggest that large on‐show enclosures with permanent access to off‐exhibit areas may compensate for the effects of visitor disturbance, and a larger number of tamarins of the same species housed close together may explain the higher cortisol levels found in tamarins living in off‐show accommodation, but further research is needed. Abstract : Research Highlights: Hand‐reared pied tamarins have higher fecal cortisol levels than parent‐reared tamarins. Pied tamarins living off‐show with more conspecific groups per building have higher salivary and fecal cortisol levels than tamarins housed on‐show in large enclosures with access to off‐exhibit areas.